The preparation of TiO2 nanoparticle photocatalysts by a flame method and their photocatalytic reactivity for the degradation of 2-propanol - Neppolian, B; Jie, HS; Ahn, JP; Park, JK; Anpo, M (CHEMICAL SOC JAPAN, 2004)
Bimetal incorporated TiO2 photocatalysts (FeZn-TiO2) prepared by a flame method showed higher catalytic activity for the degradation of 2-propanol diluted with water as compared with mono-metal incorporated or unincorporated TiO2. Using this flame method, the parameters such as a particle size, the crystallinity as well as the anatase and rutile phase ratio, which are important factors to determine the photocatalytic activity of TiO2, could be controlled without calcination of the catalysts.
Keywords: VISIBLE-LIGHT; PARTICLES